Improvement on the uniformity of deep reactive ion etch for electrically isolated silicon-based substrates. (1st April 2022) - Hu, Xiao; Zhen, Zhihan; Sun, Guotao; Wang, Qingkang; Huang, Qiyu
Abstract: Substrate-free micro-electro-mechanical systems (MEMS) devices are becoming the hotspots for microsystems. The fabrication of substrate-free MEMS devices usually involves the release of backside silicon by the inductively coupled plasma deep reactive ion etch (ICP-DRIE) process. However, when using DRIE to etch electrically isolated samples, significant non-uniformity in the etch profile were often observed. Compared to grounded silicon samples, the electrically isolated counterparts after DRIE showed a faster etch rate at the edge and a slower one in the center. This phenomenon is believed to be caused by the interaction between the deflection of charge-bearing ions entering the aperture region and the accumulated charges on the sidewall during DRIE. Simulation results with ICP showed that the electric field and ion distribution can be affected in electrically isolated substrates. After the isolated samples were electrically grounded, the charge accumulation on the sidewall was reduced and 12% etch uniformity was obtained. This technique helps in the fabrication of substrate-free MEMS devices.